Diversity of barley accessions from the Asian part of Russia in greenbug resistance - E. E. Radchenko; R. A. Abdullaev; K. D. Dyatlova; D. E. Akimova; I. A. Zveinek (Труды по прикладной ботанике, генетике и селекции)
Background. The use of barley cultivars resistant to greenbug (Schizaphis graminum Rondani) is an effective, economical and ecology-friendly way to control the dangerous phytophage. The insect is able to overcome the resistance of the host plant, which necessitates a relentless search for new genes to ensure reliable protection of barley fields from the pest.Materials and methods. Resistance to the Krasnodar greenbug population was assessed in 345 barley accessions from the Asian part of Russia. Besides, resistance to S. graminum was studied in cv. ‘Post’ (carrier of the Rsg1 gene), a pure line derived from cv. ‘Onokhoisky’ (k-16626, Buryatia) heterogeneous for this trait, and landraces from Mongolia (k-3885, k-3904, and k-4080). Juvenile plants were infested with aphids in the laboratory, and when a susceptible control died, the damage to experimental barley accessions was assessed using a scoring scale. Genetic control of greenbug resistance in the line derived from cv. ‘Onokhoisky’ was studied using the insect’s test clones and an analysis of the segregation in F2 hybrids from crossing the resistant line with cv. ‘Belogorsky’ susceptible to the aphid, when the plants were infested with the Krasnodar population of the phytophage and with clones of S. graminum.Results and conclusions. We identified 7 accessions heterogeneous for aphid resistance. Among them, plants with a high level of greenbug resistance were found in three landraces from Tuva (k-14714, k-14718, and k-14733). Resistance was also clearly expressed in the line derived from cv. ‘Onokhoisky’. This cultivar is protected by a dominant allele that differs from the previously identified Rsg1, as well as from the alleles found in Mongolian landraces k-3904, k-4080, and k-3885. ‘Onokhoisky’ also has genes with low expressivity, which manifest themselves when the main gene for resistance to S. graminum appears ineffective.